2009
DOI: 10.1002/pssc.200881155
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of excitonic emission in CuInSe2

Abstract: Radiative recombination processes in CuInSe2 (CIS) single crystals grown by the, vertical Bridgman technique were studied using photoluminescence (PL) and reflectance (RF) spectroscopies at temperatures from 4.2 to 60 K, and excitation intensity from 0.6 to 30 W/cm(2). Study of the quenching parameters of the A and B freeo and first three bound-excitons (M1, M2 and M3) in high-quality CuInSe2 single crystal leads to estimates for the binding energy of the A (7.7 meV) and B (7.9 meV) free excitons as well as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Figure shows the temperature dependence of the integrated intensities of the resolved spectra for FX and BX. The measured data for BX were fitted based on the following expression : I(T)=I01+Cexptrue(Enormalatrue/kTtrue) where I ( T ) is the integrated PL intensity, C is a pre‐exponential factor, T is temperature, and E a is the thermal activation energy for bound‐exciton luminescence. The thermal activation energy of BX was estimated to be 9 meV.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the temperature dependence of the integrated intensities of the resolved spectra for FX and BX. The measured data for BX were fitted based on the following expression : I(T)=I01+Cexptrue(Enormalatrue/kTtrue) where I ( T ) is the integrated PL intensity, C is a pre‐exponential factor, T is temperature, and E a is the thermal activation energy for bound‐exciton luminescence. The thermal activation energy of BX was estimated to be 9 meV.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental attempts to determine the free exciton binding energies E b in CuInSe 2 have been carried out by analyzing either the temperature quenching of the excitonic photoluminescence ͑PL͒ emission intensity 7,9 or diamagnetic shifts under the influence of magnetic fields. 10 The quenching characteristics of the A and B excitons are rather complex due to the small energy splitting and proximity of shallow bound excitons and thus values of E b determined by this method cannot be considered as reliable.…”
mentioning
confidence: 99%
“…More details on the experimental set ups can be found elsewhere. 9,10,12 The near band gap region of the PL and RF spectra taken in CuInSe 2 at 4.2K and 6K, respectively, using nonpolarized light, are shown in Figs. 1͑a͒ and 1͑b͒, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,[19][20][21] Temperature and excitation power dependent PL measurements of such excitonic features would provide important information about the free excitons and on the nature of defects associated with the bound excitons. 22,23 Yakushev et al 24 reported an analysis of the temperature and excitation power dependence of the free excitons associated with the A and B valence sub-bands, and of the first three bound excitons. Although the quality of the CuInSe 2 in that investigation was high enough to resolve the A and B free excitons, the resolution of the different bound exciton lines was limited.…”
Section: Introductionmentioning
confidence: 99%